2021
DOI: 10.1101/2021.03.24.435771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D visualization of SARS-CoV-2 infection and receptor distribution in Syrian hamster lung lobes display distinct spatial arrangements

Abstract: SARS-CoV-2 attaches to angiotensin-converting enzyme 2 (ACE2) to gain entry into cells after which the spike protein is cleaved by the transmembrane serine protease 2 (TMPRRS2) to facilitate viral-host membrane fusion. ACE2 and TMPRRS2 expression profiles have been analyzed at the genomic, transcriptomic, and single-cell RNAseq level, however, biologically relevant protein receptor organization in whole tissues is still poorly understood. To describe the organ-level architecture of receptor expression, related… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Samples for whole imaging analysis were prepared following the method of iDISCO as previously described with minor modifications 39 . Lung tissues at 4 dpi were fixed in 3.7% formaldehyde in PBS.…”
Section: Light Sheet Microscopymentioning
confidence: 99%
“…Samples for whole imaging analysis were prepared following the method of iDISCO as previously described with minor modifications 39 . Lung tissues at 4 dpi were fixed in 3.7% formaldehyde in PBS.…”
Section: Light Sheet Microscopymentioning
confidence: 99%
“…Transcriptomic results suggested that transmembrane serine protease 2 is expressed in higher concentrations and is more widely distributed than ACE2. Only in places where both coexisted, pulmonary middle lobe, tertiary bronchioles, and in places at the interface between bronchioles and alveoli, infection was observed [ 93 ].…”
Section: Animal Modelsmentioning
confidence: 99%